IMPLEMENTATION OF THE ONE-STOP INTEGRATED SERVICE (LTSA) PROGRAM TO PROTECT INDONESIAN MIGRANT WORKERS (PMI) IN SUKABUMI DISTRICT - Syahrillah, Helmalia Isna; Mulyadi, Andi; Amirulloh, M Rijal (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
The purpose of this study was to determine the implementation of the one-stop integrated service program (LTSA) in the effort to protect Indonesian migrant workers (PMI) in Sukabumi Regency. This research uses a qualitative method with a phenomenological approach with data collection techniques of observation, interviews and documentation. Data analysis was carried out by the process of data reduction, data presentation and conclusion drawing/verification. The results of this study are measured by indicators of implementation by Charles O Jones (1996), namely organization, interpretation and application. The results of this study are that the implementation of the program involves many parties, where inter-agency cooperation is important to ensure service integration and provide maximum benefits to the community. Then the application of the LTSA program for the protection of migrant workers is to pay attention to important aspects such as justice, non-discrimination, confidentiality and active participation of migrant workers, this aims to minimize the form of exploitation by irresponsible individuals. The implementation of the program is still faced with the obstacle that there are still illegal migrant workers who are exploited or get violence due to departure and work abroad not according to existing procedures.